Association between CAM 5.2 and anti-CD1a reactivity in lymph nodes and gastrointestinal tract epithelium. Issue 3 (March 1989) - Jack, A S; Grigor, I; O'Brien, C J; McMeekin, W; Lewis, F; McNicol, A M
Abstract : Immunocytochemical studies, using the antibodies CAM 5.2 and NA1/34 (CD1a), were performed on normal lymphoid tissue and malignant lymphomas. A population of dendritic cells in the paracortex of lymph nodes and in T cell lymphomas reacted with both antibodies. Colocalisation with antibodies was also found in gastrointestinal epithelium. Immune blotting shows that the likely basis of this reactivity is a 12 kilodalton peptide which is recognised by both antibodies. This is almost certainly the beta t peptide which has been described as the light chain of CD1a.